A study on entrepreneurial intention among information technology technopreneurs - Abd Rozan, Mohd Zaidi (2001)
The purpose of the study is to investigate entrepreneurial intention among information technology technopreneurs. The model of the study is based on Shapero’s model of entrepreneurial event. Variables included in this model are Perceived Desirability, Propensity for Proactive Behaviour and Breadth and Positiveness of Past Entrepreneurial Experience that contributed towards entrepreneurial intentions for technopreneurs. The differences in values and cultures were believed to affect their entrepreneurial behaviour and intention. These served as a building block on the upbringing of an entrepreneur. Hence, a test was needed to prove this relationship. In this project, tests to compare entrepreneurial intention between three major ethnic groups in Malaysia (Malays, Chinese and Indians) were done. Self-report questionnaires were used as a survey instrument for 129 Information Technology Technopreneurs from Johor Bahru and Kuala Lumpur. The data were analyzed using custom developed software. The results indicated that perceived desirability and propensity for proactive behavior were positively related to the formation of entrepreneurial intentions. In addition, positiveness of past entrepreneurial experiences also supported positively to the perceived desirability of starting a business. It was also found that there were no significant differences on the perception of IT Technopreneurs’ towards Propensity for Proactive Behaviour and Breadth and Positiveness of Past Entrepreneurial Experience related to Race. Only Perceived Desirability showed significant values in relation to Race. Based on this study, it showed that a specific way to view entrepreneurial intention towards starting a business and the exposure to technopreneurship assessment were the practical implications which assisted entrepreneurs’ educators to develop IT techopreneurial programs and decision making among venture capitalists.